The Use of Information Systems for Regulation of Gas Engine Operating Parameters. Issue 1 (January 2021) - Kalwar, A; Kurdziel, F; Pytel, K; Gumula, S; Lobur, M; Melnyk, M
Abstract: The purpose of the work is to indicate the possibility of using selected IT systems to analyse work and regulate operating parameters of gas engines. An additional task of the work is to indicate new possibilities of using IT systems in power plants. The publication shows the development of industrial information systems in recent years. It is shown how these systems are used for direct control and adjustment of operational parameters of power equipment, ranging from water boilers to steam boilers, turbines and cogeneration aggregates. These systems implement technical safeguards and can be used to analyse work characteristics in an appropriate configuration. The more elaborate energy systems, the wider the scope of use of IT systems. Due to the full automation and control of cogeneration gas-powered power generators, an automatic heating water flow control system through heat exchangers can be used in these installations. This solution requires the expansion of the heating water pumping system with pumping sets with inverters and fittings of the pumping station with remote control.